Interprofessional education’s readiness among Brazilian medical students / Interprofessionelle Bildung: Bereitschaft unter brasilianischen Medizinstudierenden - Secreti Prevedello Alexandra; dos Santos Fernanda; Reisdorfer Emilene (International Journal of Health Professions)
The study examines the readiness for shared learning based on interprofessional education (IPE) among Brazilian medical students participating in preceptorship programs. A total of 642 students from all six medical courses across a state in Brazil completed the Readiness for Interprofessional Learning Scale (RIPLS) and a sociodemographic questionnaire. The results, analyzed across three RIPLS factors—teamwork and collaboration, professional identity, and patient-centered care—reveal a positive inclination toward collaborative learning, though each factor was influenced by different variables. Teamwork and collaboration (factor 1) were significantly associated with gender, medical program semester, prior teamwork experience, and current clinical practice. Professional identity (factor 2) was shaped by gender, prior bachelor’s degree, type of university (public or private), and medical program semester. Patient-centered care (factor 3) showed significant relationships with gender, prior bachelor’s degree, type of university, medical program semester, and current clinical practice. These findings highlight the importance of acknowledging various demographic and educational variables when assessing student readiness for shared learning. Such insights can help medical programs refine their curricula and develop educational strategies to promote IPE, fostering collaborative healthcare practice in alignment with both national and international guidelines.